The GTPase stimulatory activities of the neurofibromatosis type 1 and the yeast IRA2 proteins are inhibited by arachidonic acid. - Golubić, M (1991)
Three proteins, GTPase activating protein (GAP), neurofibromatosis 1 (NF1) and the yeast inhibitory regulator of the RAS-cAMP pathway (IRA2), have the ability to stimulate the GTPase activity of Ras proteins from higher animals or yeast. Previous studies indicate that certain lipids are able to inhibit this activity associated with the mammalian GAP protein. Inhibition of GAP would be expected to biologically activate Ras protein. In these studies arachidonic acid is shown also to inhibit the activity of the catalytic fragments of the other two proteins, mammalian NF1 and the yeast IRA2 proteins. In addition, phosphatidic acid (containing arachidonic and stearic acid) was inhibitory for the catalytic fragment of NF1 protein, but did not inhibit the catalytic fragments of GAP or IRA2 proteins. These observations emphasize the biochemical similarity of these proteins and provide support for the suggestion that lipids might play an important role in their biological control, and therefore also in the control of Ras activity and cellular proliferation.